2004
DOI: 10.2320/matertrans.45.3102
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Transport and Thermoelectric Properties of PbTe Prepared by HPHT

Abstract: In this paper, n-type lead telluride (PbTe) compounds without doping were sucessfully prepared at high pressure and high temperature (HPHT). The carrier type was induced by the effect of pressure. The results of the electrical conductivity, Seebeck coefficient, thermal conductivity for n-type PbTe, which were measured at room temperature, show that the PbTe samples prepared by HPHT exhibit the same characteristics as heavily doped semiconductors. The figure-of-merit, Z, of 5:46 Â 10 À4 K À1 was obtained, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
23
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 17 publications
5
23
1
Order By: Relevance
“…7) Moreover, these undoped PbTe samples exhibit the same characteristics as the heavily doped PbTe samples. 8) In this result, the high TE performance of PbTe, which is induced by the electronic topological transition (ETT) under high pressure, 9) have been successfully obtained at room-temperature by HPHT. Besides the pressure-tuning, the ETT could be also induced by alloying.…”
Section: Introductionmentioning
confidence: 80%
“…7) Moreover, these undoped PbTe samples exhibit the same characteristics as the heavily doped PbTe samples. 8) In this result, the high TE performance of PbTe, which is induced by the electronic topological transition (ETT) under high pressure, 9) have been successfully obtained at room-temperature by HPHT. Besides the pressure-tuning, the ETT could be also induced by alloying.…”
Section: Introductionmentioning
confidence: 80%
“…[18][19][20][31][32][33] In a few other cases, high pressure is applied in conjunction with high temperature to obtain specific phases and/or to attain special electronic band structures. [34][35][36][37][38] Unlike most other chemical reactions that are ignited and sustained by heat, the process we herein report is basically mechanochemical. In this work, stoichiometric admixture of Cu (4 N, 200 mesh) and S/Se (5 N, 100 mesh) powders is hand ground in an agate mortar and cold pressed into a pellet of 15 mm diameter.…”
mentioning
confidence: 99%
“…The results indicate that the HPHT method has potential application in obtaining thermoelectric materials with good performance. 8 In 2007, Kraemer et al studied the phase stability of the skutterudite compound CoSb 3 at pressures above 20 GPa. They found that the cobalt antimonide undergoes an irreversible transition to another phase with a volume increase at ambient pressure.…”
Section: Introductionmentioning
confidence: 99%